DAKWAH DALAM ARUS GLOBALISASI MEDIA: PELUANG DAN TANTANGAN - Muhammad Haramain (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2017)
The dynamics of Islamic media have a fundamental problem in the position of global communications controlled by Western hegemony so strong and become the main players. Islam does not have a significant position. Countries that have a majority Muslim people much depend on the information provided by the West, especially the United States. In terms of communication media, generally third world countries, including Islam only as consumers whose utilization has not been maximally felt by all citizens. Moreover, being a producer in creating communication media, it seems too far to be expected. The implications arising from such an Islamic position, in global communication, of course, Islam does not yet have the power to play a significant role. The presence of Islam in global communications is only limited to the discourse that has great potential to rise. In order to further enhance its role in global communications, Muslims should make systematic efforts to catch up. Efforts should be made are: First, make the teachings of Islam as a source of vitality of civilization; Second, establishing harmonious cooperation between Islam and the West, especially the media; Third, improve the ability of Muslims in the mastery of science and technology, especially communications and build world news agencies; Fourth, Islamic institutions can play their part in the global arena; Fifth, cooperation between Islamic countries needs to be improved.